Miscellanea Herpetologica Sanctithomae, with a provisional checklist of the terrestrial herpetofauna of São Tomé, Príncipe and Annobon islands - Ceríaco, Luis M. P.; Marques, Mariana P.; Bauer, Aaron M. (Zootaxa, 2018)
Five problematic cases regarding the presence of reptile taxa on the island of São Tomé (Gulf of Guinea) are reviewed. These cases deal with 1) the past presence of crocodilians in the island, 2) the putative type locality of Dipsas pulverulenta Fischer, 1856, 3) the dubious presence of a mamba (genus Dendroaspis) on the island, 4) an erroneous reference to the presence of Gastropyxis smaragdina, and 5) two specimens (Psammophis lineatus and Psammophis elegans) from Carl Weiss collection, currently deposited in the Zoological Museum of Hamburg and wrongly labelled as being from São Tomé island. A provisional checklist to the terrestrial herpetofauna of the three oceanic islands of the Gulf of Guinea—São Tomé, Príncipe and Annobon—is presented in order to clarify the current numbers of the endemics of each island, as well as to review and present current research.